Subjective assessment of vision quality by patients over 35 after excimer laser and orthokeratological correction of myopia according to a survey - V. V. Neroev; M. D. Sengaeva; E. P. Tarutta; N. V. Khodzhabekyan; A. T. Khandzhyan; A. V. Ivanova; K. B. Letnikova; A. S. Sklyarova (Российский офтальмологический журнал)
Purpose:  to analyze the results of a survey aimed at assessing the patients’satisfaction with the results of excimer laser or orthokeratological correction of myopia.     Materials and methods.  135 patients aged 35 to 50 took part in a satisfaction survey: 105 after excimer laser and 30 after orthokeratological correction of myopia. Excimer laser surgery was performed with planned binocular hypocorrection within -0.75 — 1.5 D depending on age. To participate in the survey, the patients signed a preliminary consent. The questionnaire asked for age, gender, occupation, self-assessment of visual functions under a variety of conditions (vision at dusk, at close distance, at far distance, while driving a vehicle, etc.), self-assessment of satisfaction with the result. The questionnaire required to answer 15 questions on a multiplechoice basis.   Results. Over 50 % of the patients have no difficulty working at close distance, at far distance, or when driving a vehicle, and do not restrict themselves in professional or everyday activities. More than 90 % of the patients would recommend excimer laser correction in binocular format with a planned hypo effect or orthokeratological correction to others. 125 out of 135 patients gave the maximum satisfaction score points.   Conclusion:  excimer laser correction of myopia with a planned hypoeffect in binocular format and orthokeratological correction can be recommended for patients over 35.